PEMANFAATAN MULTIMEDIA SIMULASI SEBAGAI MEDIA PENYULUHAN BERBASIS ANIMASI 3D - Much Rifqi Maulana (STEKOM PRESS, 2016)
Freshwater fish farming extension activity is one of the activities at UPT Karanganyar Fish Seed Center (BBI). In freshwater fish farming extension activities at the exposure session at UPT Balai Balai Ikan Ikan (BBI), they still used the lecture model and did not use other extension media. This resulted in extension participants becoming less familiar with the exposure material they obtained. Participants had difficulty in describing counseling materials. This has become an obstacle for the extension team in delivering the counseling material. Utilization of Simulated Multimedia as a 3D Animation-Based Counseling Media, can facilitate the counseling team in providing material exposure explanation on how to cultivate freshwater fish. By utilizing 3D Animation-based Mutlimedia Simulation can help extension participants in understanding the depiction of extension material to be implemented at the practice stage of freshwater fish farming. This is evidenced by using a user test, 40% of 25 respondents who stated that by utilizing multimedia simulation based on 3D assimilation, it is feasible to be used as an extension media for freshwater fish farming.